2021
DOI: 10.7759/cureus.20088
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Impaired Wound Healing Among Patients With Major Head and Neck Free-Flap Reconstruction in the Setting of COVID-19 Infection

Abstract: Due to the microvascular effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), head and neck reconstructive surgeries utilizing free tissue transfers may be profoundly affected by SARS-CoV-2 infection in the immediate postoperative period. Our objective is to describe two adult patients who developed SARS-CoV-2 after undergoing relatively uncomplicated segmental mandibulectomies. In both cases, the patients were initially negative for SARS-CoV-2, underwent relatively uncomplicated segmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“… [18] , [19] The binding of SARS-CoV-2 to ACE2 increases levels of angiotensin II (Ang II), a potent vasoconstrictor and pro-inflammatory molecule which exerts oxidative stress, mitochondrial dysfunction, endothelial cell damage, hypercoagulation and thrombosis (via free radical generation), and jeopardise proper neovascularisation for wound healing. 2 High levels of serum plasminogen activator inhibitor-1 (PAI-1) and D-dimers are consistent with microthrombi observed in COVID-19 patient autopsies. 19 Clinically, Inouye et al 2 reported free flap failure in patients with SARS-CoV-2, and Talmor et al .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“… [18] , [19] The binding of SARS-CoV-2 to ACE2 increases levels of angiotensin II (Ang II), a potent vasoconstrictor and pro-inflammatory molecule which exerts oxidative stress, mitochondrial dysfunction, endothelial cell damage, hypercoagulation and thrombosis (via free radical generation), and jeopardise proper neovascularisation for wound healing. 2 High levels of serum plasminogen activator inhibitor-1 (PAI-1) and D-dimers are consistent with microthrombi observed in COVID-19 patient autopsies. 19 Clinically, Inouye et al 2 reported free flap failure in patients with SARS-CoV-2, and Talmor et al .…”
Section: Discussionmentioning
confidence: 58%
“… 2 High levels of serum plasminogen activator inhibitor-1 (PAI-1) and D-dimers are consistent with microthrombi observed in COVID-19 patient autopsies. 19 Clinically, Inouye et al 2 reported free flap failure in patients with SARS-CoV-2, and Talmor et al . 20 described pedicled nasoseptal flap necrosis and failure due to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“… 43 Inouye and colleagues also presented two SARS-CoV-2 associated cases of impaired wound healing in patients undergoing head and neck free flap reconstruction. 44 Benmoussa et. al also noted free flap failure in a SARS-CoV-2 positive patient undergoing gingival mandibular carcinoma resection and reconstruction.…”
Section: Endoscopic Skull Base Surgerymentioning
confidence: 99%